2020
DOI: 10.3390/ijerph17249540
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in Primary School Children: The Relationship between Victimization and Perception of Being a Victim

Abstract: This study aims to investigate victimization of bullying in primary school children, as well as its relationship with children’s perception of being a victim. In a sample of 4646 students from 3rd to 6th grade, we evaluated children’s victimization and cybervictimization behaviors, and children were also asked whether they had been victims of bullying or cyberbullying. From the participants, 36.7% were victims, and 4.4% cybervictims. In addition, 24.2% had a perception of being a victim, and 4.9% a perception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Moreover, different victimization forms predicted suicidal thoughts and behaviors in middle school students (Wang et al, 2018), in concordance with results reported in higher students (Kowalski et al, 2014), and elicited feelings such as students' sadness or anger, being greater for victimization than CV (Wright, 2017a). Other studies concluded that CV could be related to victimization (Sidera et al, 2020). Elementary students who witnessed CB showed higher levels of anxiety than bullying witnesses (Doumas & Midgett, 2020).…”
Section: Findings/conclusion On the Connections Between Bullying And Cbsupporting
confidence: 82%
“…Moreover, different victimization forms predicted suicidal thoughts and behaviors in middle school students (Wang et al, 2018), in concordance with results reported in higher students (Kowalski et al, 2014), and elicited feelings such as students' sadness or anger, being greater for victimization than CV (Wright, 2017a). Other studies concluded that CV could be related to victimization (Sidera et al, 2020). Elementary students who witnessed CB showed higher levels of anxiety than bullying witnesses (Doumas & Midgett, 2020).…”
Section: Findings/conclusion On the Connections Between Bullying And Cbsupporting
confidence: 82%
“…Escortell et al [ 29 ], assessing 15 electronic harassment behaviours in a sample of 548 Spanish students aged 10 to 13 from Alicante, found that 18% of the participants reported suffering cybervictimization. In a series of studies with students in years 3 to 6 of primary school in Catalonia (Spain), Sidera et al found that 14.4% of the participants have suffered at least one online aggression in the last month [ 30 ] and 4.4% were cyber victims with a minimum frequency of once or twice a month [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that students with DLD and RD have a higher prevalence of peer problems, poorer acceptance of their classmates, lower quality and quantity of friendships, and larger vulnerability to peer rejection ( Laws et al, 2012 ; Mok et al, 2014 ; Lloyd-Esenkaya et al, 2020 ). However, the accumulating evidence indicates the necessity to distinguish between the perspectives of different reporters and consider the students’ characteristics ( Sidera et al, 2020 ; Gough Kenyon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Victimized students may not acknowledge the experience of rejection or victimization, as seems to happen to the children with DLD in our sample (who are rated as more victimized by others, but not by themselves). In this vein, some studies have found that only a low percentage of adolescents (between 16 and 32%) who are categorized as bullying victims perceive themselves as victims ( Hwang et al, 2017 ; Sidera et al, 2020 ). Sidera et al (2020) explain that this misperception can be related to the type and quantity of bullying actions that someone experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation